KEBERADAAN PERJANJIAN PARTISIPASI PROMOSI - Dwi Tatak Subagiyo (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
The concept of promotion participation agreement should apply the system in the 3rd book of Civil Law (KUHP Perdata). The parties involved have reached and agreement with element of agreement. Therefore, the legal rule in the promotion participation agreement has almost entirely stated in this agreement. As a matter of fact, there still a possibility for the parties that chose not follow the rule, to make the agreement of their own.